mRNA-expression of KRT5 and KRT20 defines distinct prognostic subgroups of muscle-invasive urothelial bladder cancer correlating with histological variants - Eckstein, Markus; Groß-Weege, Matthias; Nitschke, Katja; Porubský, Štefan; Erben, Philipp (International journal of molecular sciences, 2018)
Recently, muscle-invasive bladder cancer (MIBC) has been subclassified by gene expression profiling, with a substantial impact on therapy response and patient outcome. We tested whether these complex molecular subtypes of MIBC can be determined by mRNA detection of keratin 5 (KRT5) and keratin 20 (KRT20). Reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) was applied to quantify gene expression of KRT5 and KRT20 using TaqMan®-based assays in 122 curatively treated MIBC patients (median age 68.0 years). Furthermore, in silico analysis of the MD Anderson Cancer Center (MDACC) cohort (GSE48277 + GSE47993) was performed. High expression of KRT5 and low expression of KRT20 were associated with significantly improved recurrence-free survival (RFS) and disease-specific survival disease specific survival (DSS: 5-year DSS for KRT5 high: 58%; 5-year DSS for KRT20 high: 29%). KRT5 and KRT20 were associated with rates of lymphovascular invasion and lymphonodal metastasis. The combination of KRT5 and KRT20 allowed identification of patients with a very poor prognosis (KRT20+/KRT5−, 5-year DSS 0%, p < 0.0001). In silico analysis of the independent MDACC cohorts revealed congruent results (5-year DSS for KRT20 low vs. high: 84% vs. 40%, p = 0.042). High KRT20-expressing tumors as well as KRT20+/KRT− tumors were significantly enriched with aggressive urothelial carcinoma variants (micropapillary, plasmacytoid, nested).
Gesehen am 06.12.2018